1975
DOI: 10.1093/ajcp/64.1.34
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Polyanions on NBT Reduction Hexose Monophosphate Shunt Activity, and Ultrastructure of Polymorphonuclear Leukocytes

Abstract: Heparin causes enhanced nitroblue tetrazolium (NBT) reduction by polymorphonuclear leukocytes (PMN's). To determine the mechanism of this stimulation, samples of 1 to 3 x 10(7) PMN's were incubated with various concentrations of heparin, chondroitin sulfate A (CSA), and chondroitin sulfate B (CSB), with and without NBT. The effect of the polyanions (PA) on PMN hexose monophosphate shunt (HMPS) activity was determined by the production of 14CO2 from glucose-1-14C by the leukocytes. NBT reduction was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

1976
1976
1986
1986

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…NBT can form aggregates with heparin and fibrinogen in plasma and these can be phagocytosed leading to reduction (Segal & Levi, 1973). Czarnetzki et aL (1975) demonstrated that the degree of NBT reduction depends on the heparin concentration in the system but we took particular care to keep this at 20 /ig per ml in all these experiments. It may be that in addition to C5a fragments and heparin fibrinogen complexes, the extra stimulation provided by zymosan is due either to its particle size or the possibility that it forms aggregates with heparin and fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…NBT can form aggregates with heparin and fibrinogen in plasma and these can be phagocytosed leading to reduction (Segal & Levi, 1973). Czarnetzki et aL (1975) demonstrated that the degree of NBT reduction depends on the heparin concentration in the system but we took particular care to keep this at 20 /ig per ml in all these experiments. It may be that in addition to C5a fragments and heparin fibrinogen complexes, the extra stimulation provided by zymosan is due either to its particle size or the possibility that it forms aggregates with heparin and fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Already in 1941 it had been stressed by KUHN and JERCHEL [6] that tetrazolium salts are suitable to demonstrate the capacity for reduction in biological systems. Concerning the NBT reduction by phagocytes it has been demonstrated that this reaction is closely linked to the stimulation of the hexose monophosphate shunt (HMPS) [7,8] in activated cells.…”
Section: Introductionmentioning
confidence: 99%
“…A viabilidade celular de todos os materiais biológicos foi avaliada por meio do teste de exclusão do azul de tripano 1% (CZARNETZKY; COWAN;BELCHER, 1975;FALLON et al, 1962;KING et al, 1959). Os resultados obtidos foram superiores a 90% de células viáveis para todos os ensaios realizados.…”
Section: Viabilidade Celularunclassified